Hypocalcaemia following total thyroidectomy: early post-operative parathyroid hormone assay as a risk stratification and management tool. Issue 3 (24th March 2014) - Islam, S; Al Maqbali, T; Howe, D; Campbell, J
Abstract Objective: To develop a practical, efficient and predictive algorithm to manage potential or actual post-operative hypocalcaemia after complete thyroidectomy, using a single post-operative parathyroid hormone assay. Methods: This paper reports a prospective study of 59 patients who underwent total or completion thyroidectomy over a period of 24 months. Parathyroid hormone levels were checked post-operatively on the day of surgery, and all patients were evaluated for hypocalcaemia both clinically and biochemically with serial corrected calcium measurements. Results: No patient with an early post-operative parathyroid hormone level of 23 ng/l or more (i.e. approximately twice the lower limit of the normal range) developed hypocalcaemia. All the patients who initially had post-operative hypocalcaemia but had an early parathyroid hormone level of 8 ng/l or more (i.e. approximately two-thirds of the lower limit of the normal range) had complete resolution of their hypocalcaemia within three months. Conclusion: Early post-operative parathyroid hormone measurement can reliably predict patients at risk of post-thyroidectomy hypocalcaemia, and predict those patients expected to recover from temporary hypocalcaemia. A suggested post-operative management algorithm is presented.